Linking sustainability and spirituality: the university with a soul - Abdul Razak, Dzulkifli; Moten, Abdul Rashid (Association for Higher Education Studies, 2023)
Higher education institutions were intended to nurture the creative potential of individuals and assist in the development of civilization. After 1945, the number of modern universities expanded, but their original purpose changed. Universities have become more business-oriented institutions. The Fourth Industrial Revolution (4IR) has changed almost every area of human activity at an unpredictable pace, challenging old paradigms and frameworks. Society scaled back education to meet market demands, and people lost their moral and intellectual dispositions. The general focus is on developing a workforce, inventive spirit, and high-tech machinery based on innovation and technology, resulting in weak ethical standards and a dangerous lack of trust in the community. Educators need to explore new and creative approaches to educational innovation to improve future learning. The need is for an education with a soul. Educators must cultivate the dual consciousness that humanizes technology through bold visions of moderation. They should help students develop a higher sense of purpose. Knowledge must be viewed from a new perspective. Knowledge must be wholesome or holistic, inclusive, sustainable and equitable in the sense that everyone has access to this special knowledge and can develop a sense of mercy, compassion and benevolence. In sum, the education system should be world-wide, inclusive, sustainable, and show mercy to all